Breeding of Insects for Biofuels Production - Leong, S.Y. (Nova Science Publishers, Inc., 2021)
Insect larvae are well known for their high lipid and protein content. Defatted insect meal, comprised primarily of protein, is used for animal feed. As a result of the surge in the exploration of a sustainable renewable energy sources, lipids extracted from insects have become one of the promising feedstock for biodiesel production. The use of insect lipids has been shown to be notably feasible for biodiesel production due to the desirable properties of lipids. The use of insects has piqued the interest of investors to establish an insect farming and processing platform. Until now, Hermetia illucens and Tenebrio molitor have been extensively farmed for mass production. Consequently, this review began with the life cycle of insects, the processing of larvae and the use of insect larvae for the production of biodiesel. Â© 2021 by Nova Science Publishers, Inc.